Rules and principles in European contract law / edited by Jacobien Rutgers, Pietro Sirena. - Rutgers, Jacobien W.; Sirena, Pietro (European contract law and theory series, 2015)
In its case law the Court of Justice of the European Union has acknowledged general principles of EU law, which have a constitutional status. In addition the Court of Justice has also recognised 'general principles of civil law', relying upon values which are traditionally rooted in the domain of private law. The pervasive use of principles, both in the case law of the Court of Justice and in other EU projects of 'soft ' and 'hard' law, challenges legal scholarship. Although the concepts of principles and rules have been widely discussed within the context of national legal orders, they need to be rethought at the European level, because the traditional view of a principle does not fit the European Union's constitutional architecture. This also applies to the general principles of civil law, for instance good faith. They also have to be redefined to be consistent with the European Union's legal order.The contributions in this book examine EU general principles and their distinction from rules both within the context of the European Union as well as of the Member States. Moreover, they focus on the relevance of EU general principles for contract law and of principles of civil law for a European contract law